Language Variations between Women and Men at SMP Muhammadiyah 3 Medan Academic Years 2017/2018 - Oktavia Lestari P (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
Abstract-This study was a verbal analysis based on gender, with differences in sample language between male and female students in junior high school muhammadiyah 3 Medan, academic years 2017/2018. Based on the data, the results are as follows: (1) Use of voice and intonation From the data, summed up as follows. (1) Language and communication problems are more important for women than men because women talk more often about men. (2) The purpose of men in the use of language tends to get something, while women tend to make connections with others. More and more men talk about data and facts, while more women talk about people, feelings, and relationships among people. (3) Women are more verbally skilled than men. (4) Differences often lead to